2013
DOI: 10.1242/jcs.122903
|View full text |Cite
|
Sign up to set email alerts
|

Compliance-induced adherens junction formation in epithelial cells and tissues is regulated by JNK

Abstract: SummaryWe demonstrate that c-Jun N-terminal kinase (JNK) responds to substrate stiffness and regulates adherens junction (AJ) formation in epithelial cells in 2D cultures and in 3D tissues in vitro and in vivo. Rigid substrates led to JNK activation and AJ disassembly, whereas soft matrices suppressed JNK activity leading to AJ formation. Expression of constitutively active JNK (MKK7-JNK1) induced AJ dissolution even on soft substrates, whereas JNK knockdown (using shJNK) induced AJ formation even on hard subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 63 publications
3
21
0
Order By: Relevance
“…For example, the rapid adherens junction disassembly of T84 and SK-CO15 cell monolayers was accompanied by JNK activation and prevented by JNK inhibition (Naydenov et al, 2009), similar to our observations in JNK-inhibited fetal ovaries. Here too, as we observed in the SP600125-treated ovaries, E-cadherin and β-catenin are upregulated when JNK function is disrupted (Lee et al, 2009;You et al, 2013). Furthermore, JNK activation has been associated with E-cadherin inactivation and cell polarity loss in Drosophila epithelial cells (Igaki et al, 2006).…”
Section: Discussionsupporting
confidence: 60%
“…For example, the rapid adherens junction disassembly of T84 and SK-CO15 cell monolayers was accompanied by JNK activation and prevented by JNK inhibition (Naydenov et al, 2009), similar to our observations in JNK-inhibited fetal ovaries. Here too, as we observed in the SP600125-treated ovaries, E-cadherin and β-catenin are upregulated when JNK function is disrupted (Lee et al, 2009;You et al, 2013). Furthermore, JNK activation has been associated with E-cadherin inactivation and cell polarity loss in Drosophila epithelial cells (Igaki et al, 2006).…”
Section: Discussionsupporting
confidence: 60%
“…Recently, our laboratory showed that substrate stiffness regulated AJ formation between epithelial cells in two-dimensional (2D) cultures and in three-dimensional (3D) epidermal tissues in vitro and in vivo by regulating the phosphorylation levels of the c-Janus N-terminal kinase (JNK) [51]. Rigid substrates led to JNK activation and AJ disassembly, while soft matrices suppressed JNK activity leading to AJ formation.…”
Section: Adherens Junctions: Signal Transduction and Mechanosensingmentioning
confidence: 99%
“… 37 It is well known that stiffness of substrates mediates the cross talk between cell-substrate and cell-cell adhesion 38 . Under low Ca 2+ concentration, epithelial cells prefer to stay as individual cells and adhere firmly on stiff substrate through integrin-mediated focal adhesion.…”
Section: Cell-cell Junction Formationmentioning
confidence: 99%